Reliability and sensitivity analysis of a system with multiple unreliable service stations and standby switching failures - Ke, Jyh-Bin; Lee, Wen-Chiung; Wang, Kuo-Hsiung (Physica A, 2007)
This paper presents the reliability and sensitivity analysis of a system with M primary units, W warm standby units, and R unreliable service stations where warm standby units switching to the primary state might fail. Failure times of primary and warm standby units are assumed to have exponential distributions, and service times of the failed units are exponentially distributed. In addition, breakdown times and repair times of the service stations also follow exponential distributions. Expressions for system reliability, R Y ( t ) , and mean time to system failure, MTTF are derived. Sensitivity analysis, relative sensitivity analysis of the system reliability and the mean time to failure, with respect to system parameters are also investigated.